Pengaruh Corporate Governance dan Insentif Eksekutif terhadap Tax Avoidance - Bagaskara, Alvie; Idawati, Wiwi (Media Ilmiah Akuntansi, 2023)
This study aims to examine the relationship between corporate governance and executive incentives on tax avoidance with profitability and leverage as control variables. This research is focused on manufacturing companies in the consumer goods sub-sector listed on the Indonesia Stock Exchange for the period 2015 - 2019. Determination of the number of samples in this study using panel data, so that a sample of 25 manufacturing companies was obtained with the data analysis method used was multiple regression analysis. The results of this study indicate that institutional ownership and audit committee have a negative and significant effect, profitability and leverage have a positive and significant effect, and executive incentives have a negative effect on tax avoidance.